Análisis del Desempeño Estudiantil en las Pruebas de Estado para Educación Media en Colombia mediante Modelos Jerárquicos Lineales - Orjuela, Jaime (Ingeniería, 2014)
In this paper, Hierarchical Lineal Models are applied for analyzing individual factors of student performance in Colombian High School Government Tests, using data from 2009 , which are the latest results publicly available from the Instituto Colombiano para el Fomento de la Educación Superior (Icfes). Initially the paper describes the data as well as assumptions for cleaning and preprocessing steps that were necessary. After that, concepts related to Hierarchical Lineal Models are introduced, and the models are applied to the data. According to the obtained results, there exists a direct relationship between non academics features and student performance, evaluated in Colombian High School Government Tests. These features (social and economic) are different between public and private schools, and also between daytime schools and other-time schools.